Measurement of WW / WZ → ℓνqq' production with the hadronically decaying boson reconstructed as one or two jets in pp collisions at √s = 8 TeV with ATLAS, and constraints on anomalous gauge couplings - Alconada Verzini, María Josefina (2017)
This paper presents a study of the production of WW or WZ boson pairs, with one W boson decaying to eν or µν and one W or Z boson decaying hadronically. The analysis uses 20.2 fb-1 of √s = 8 TeV pp collision data, collected by the ATLAS detector at the Large Hadron Collider. Cross-sections for WW / WZ production are measured in high-pT fiducial regions defined close to the experimental event selection. The cross-section is measured for the case where the hadronically decaying boson is reconstructed as two resolved jets, and the case where it is reconstructed as a single jet. The transverse momentum distribution of the hadronically decaying boson is used to search for new physics. Observations are consistent with the Standard Model predictions, and 95% confidence intervals are calculated for parameters describing anomalous triple gauge-boson couplings.